2017
DOI: 10.1080/21691401.2017.1332634
|View full text |Cite
|
Sign up to set email alerts
|

Green approach for synthesis of gold nanoparticles from Nigella arvensis leaf extract and evaluation of their antibacterial, antioxidant, cytotoxicity and catalytic activities

Abstract: In the present work, we studied the reduction of gold ions into gold nanoparticles using Nigella arvensis leaf extract in the one-step green synthesis method. The formation of N. arvensis gold nanoparticles (NA-GNPs) was confirmed by UV-Vis spectroscopy, XRD, FT-IR and TEM analyses. The XRD pattern confirmed the crystal structure of NA-GNPs, and TEM image showed the small size (3-37 nm) and almost spherical shape of NA-GNPs. NA-GNPs have not shown enhanced antioxidant properties compared to the plant extract w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 51 publications
(56 reference statements)
1
46
0
Order By: Relevance
“…In this way, it can be applied plants, algae, bacteria and fungi as reducing and stabilizing precursors [7]. Among these organisms, plants have advantages of high availability, biocompatibility and biodegradability [8]. Artemisia L. belongs to the large family Asteraceae (Compositae) with approximately 20,000 species in 1000 genera.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, it can be applied plants, algae, bacteria and fungi as reducing and stabilizing precursors [7]. Among these organisms, plants have advantages of high availability, biocompatibility and biodegradability [8]. Artemisia L. belongs to the large family Asteraceae (Compositae) with approximately 20,000 species in 1000 genera.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf extracts contain a wide range of biomolecules and metabolites, such as terpenoids [act as reducing agents and stabilizers of nanosuspensions in the process of phytosynthesis. It is assumed that the phenolic compounds of plants [44,45], such flavonoids as quercetin, genistein, kaempferol, and proanthocyanidin in particular [46], are primarily responsible for the synthesis of AuNPs.Fourier transform infrared spectroscopy showed that hydroxyl (-OH) [19,41] and carbonyl (= CO) [45] groups of compounds present in the plants [24,[47][48][49][50][51]] play a key role in the formation of metal nanoparticles in the photosynthesis process. According to many researchers, the mechanism of phytosynthesis is quite simple: the precursor (Au (III)) is reduced by plant phenolic compounds to AuNPs as a result of the redox reaction with the formation of a phyto-functional coating (phyto-AuNPs) on the surface of the nanoparticles, which protects the particles from aggregation [52][53][54].Despite significant successes in the field of phytosynthesis of AuNPs and metal nanoparticles in general, there is a problem of controllability of phytosynthesis and prediction of the AuNPs properties.…”
mentioning
confidence: 99%
“…64 Chahardoli et al (2017) showed that the percentage cell death of MCF-7 and H1299 cells slowly increases with the addition of AuNPs concentration and significantly inhibited the cancer cells with the lowest amount of AuNPs. 65 However, earlier studies have been reported that interactions between different types of nanoparticles and cells are depended on shape, size and surface chemistry of the nanoparticles and the nature of cells. 2,66,67 MB is a thiazine dye that used for analysis of amounts of sulfide ions in aquatic samples.…”
Section: Discussionmentioning
confidence: 99%
“…Similar catalytic activity has been reported by Chahardoli et al (2017) for green synthesized AuNPs from Nigella arvensis which caused 44% degradation of MB dye. 65 They stated that AuNPs as electron transfer mediators acted as redox catalysts between the plant biomolecules and the dyes that are often called as electron relay effect. 65 Furthermore, synthesized AuNPs using Piper longum showed catalytic activity against MB after 28 hr up to 64% degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation